Trimethylaluminum Diffusion in PMMA Thin Films during Sequential Infiltration Synthesis: In Situ Dynamic Spectroscopic Ellipsometric Investigation. Issue 20 (14th August 2018) - Cianci, Elena; Nazzari, Daniele; Seguini, Gabriele; Perego, Michele
Abstract: Sequential infiltration synthesis (SIS) provides a successful route to grow inorganic materials into polymeric films by penetrating of gaseous precursors into the polymer, both in order to enhance the functional properties of the polymer creating an organic–inorganic hybrid material, and to fabricate inorganic nanostructures when infiltrating in patterned polymer films or in self‐assembled block copolymers. A SIS process consists in a controlled sequence of metal–organic precursor and coreactant vapor exposure cycles of the polymer films in an evacuated reactor. Here, a study of the SIS process of alumina using trimethylaluminum (TMA) and H2 O in various polymer films using in situ dynamic spectroscopic ellipsometry (SE) is reported. In situ dynamic SE enables time‐resolved monitoring of the polymer swelling, which is relevant to the diffusion and retains the metal precursor into the polymer itself. Diffusion coefficients of TMA in poly(methylmethacrylate) (PMMA) are extracted, investigating the swelling of pristine PMMA films during TMA infiltration and shown to be dependent on polymer molecular weight. In situ dynamic SE allows to control the SIS process, tuning it from an atomic layer deposition – like process for long purge to a chemical vapor deposition – like process selectively confined inside the polymer films. Abstract : Sequential infiltration synthesis of Al2 O3 in poly(methylmethacrylate) (PMMA) and polystyrene polymer films is monitored by in situ dynamic spectroscopic ellipsometry. Infiltration of trimethylaluminum (TMA) in PMMA results in large polymer swelling, according to initial Fickian diffusion of TMA into the polymer with diffusion coefficient depending on polymer molecular weight.